P2X7 promotes metastatic spreading and triggers release of miRNA-containing exosomes and microvesicles from melanoma cells - Pegoraro, Anna; De Marchi, Elena; Ferracin, Manuela; Orioli, Elisa; Zanoni, Michele; Bassi, Cristian; Tesei, Anna; Capece, Marina; Dika, Emi; Negrini, Massimo; Di Virgilio, Francesco; Adinolfi, Elena (Cell death & disease, 2021)
Tumor growth and metastatic spreading are heavily affected by the P2X7 receptor as well as microvesicles and exosomes release into the tumor microenvironment. P2X7 receptor stimulation is known to trigger vesicular release from immune and central nervous system cells. However, P2X7 role in microvesicles and exosomes delivery from tumor cells was never analyzed in depth. Here we show that P2X7 is overexpressed in patients affected by metastatic malignant melanoma and that its expression closely correlates with reduced overall survival. Antagonism of melanoma cell-expressed P2X7 receptor inhibited in vitro anchorage-independent growth and migration and in vivo dissemination and lung metastasis formation. P2X7 stimulation triggered the release of miRNA-containing microvesicles and exosomes from melanoma cells, profoundly altering the nature of their miRNA content, as well as their dimensions and quantity. Among the more than 200 miRNAs that we found up-or-down-modulated for each vesicular fraction tested, we identified three miRNAs, miR-495-3p, miR-376c-3p, and miR-6730-3p, that were enriched in both the exosome and microvesicle fraction in a P2X7-dependent fashion. Interestingly, upon transfection, these miRNAs promoted melanoma cell growth or migration, and their vesicular release was minimized by P2X7 antagonism. Our data unveil an exosome/microvesicle and miRNA-dependent mechanism for the pro-metastatic activity of the P2X7 receptor and highlight this receptor as a suitable prognostic biomarker and therapeutic target in malignant melanoma.